Sistem Informasi Pengantaran Pasien Instalasi Rawat Darurat RSUP dr. Soeradji Tirtonegoro Klaten - Susena, Edy; Budiono (Journal Health Information Management Indonesian (JHIMI), 2022)
Constraints faced in Delivering Emergency Room Patients dr. Soeradji Tirtonegoro Klaten is the absence of an information system that provides information about the availability of patient admission tools in the form of wheelchairs / wheeled beds, patient diagnoses to be handled regarding the disease they suffer from the usual, moderate, severe categories, and information on patient ward rooms (empty / full). This causes if there is a patient who comes for intensive treatment and requires a medium of delivery in the form of a wheelchair / wheeled bed, the officer cannot know quickly because he has to wait for the patient to come, as well as the officers' ignorance quickly about the patient's condition at that time in the form of a diagnosis of common disease, moderate , or severe because from the diagnosis the officer can be careful in delivering the ward room, and another obstacle is the information on the availability of the ward, when the officer brings the patient to the ward room, sometimes all the rooms are full so they are transferred to another room besides the emergency room, even though the distance between the emergency room and other rooms are far enough away to put the patient's health at risk. In overcoming the existing problem the writer makes an information system using data collection methods by observation, interviews, and documentation. While the author's system development method uses the waterfall method, the database uses MySQL, and the Laravel framework. The result of this research is an information system for Emergency Room Patient Delivery dr. Soeradji Tirtonegoro Klaten based on a website with a MySQL database and the Laravel framework, for testing using the blackbox method with the results of the performance of each button being successful / successful according to its function